PENERAPAN MULTIMEDIA DALAM PEMBELAJARAN DI TK ANANDA BAGAN BATU - Volvo Sihombing ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstrack - The interest in reading children in a conventional manner is currently less attractive to the age of kindergarten children (tk) so that technological tools are perceived visually and in motion so that children are more interested and easy in the learning process. The development of multimedia applications as a means of assisting devices helps children to be more creative and interested in learning and can stimulate the thinking of children in the field of education taught in children's garden schools. The programming language used is the VB programming language and is supported with photoshop in the design of existing images as well as sound recorders for recording sound built into the application.   Keywords - multimedia, vb, tk